Distribution of HLA-B Locus Antigens in Patients with Psoriatic Arthritis in Bangladesh (Bangladesh Journal of Medical Microbiology, 2018)
This study was designed to investigate the distribution of HLA-B locus antigens in patients with psoriatic arthritis (PsA) in Bangladesh and identify HLA markers related to disease manifestation in PsA. HLA-B typing was carried out by polymerase chain reaction (PCR) with sequence specific primers in a group of 50 consecutive PsA patients. The reports of HLA-B locus antigens typing were collected from 50 ages and sex matched unrelated healthy donors as controls. A total of 17 HLA-B locus antigens were determined in both patients and controls. The most common antigen was B*15 (34%) followed by B*07 (26%), B*27 (24%), B*38 (20%). Human leukocyte antigens B*07, B*27 and B*38 alleles were found to be significantly prevalent in PsA patients compared with healthy controls. We found a statistically significant association between spondylitis pattern and the presence of HLA-B*27. PsA in Bangladeshi patients seems to be associated with the presence of B*07, B*27 and B*38 alleles.Bangladesh J Med Microbiol 2018; 12 (2): 14-20